Non-radiative wireless energy transfer with single layer dual-band printed spiral resonator - Lai Ly Pon; Sharul Kamal Abdul Rahim; Chee Yen Leow; Tien Han Chua (Institute of Advanced Engineering and Science, 2019)
Accomplishing equilibrium in terms of transfer efficiency for dual-band wireless energy transfer (WET) system remains as one of key concerns particularly in the implementation of a single transmitter device which supports simultaneous energy and data transfer functionality. Three stages of design method are discussed in addressing the aforementioned concern. A single layer dual-band printed spiral resonator for non-radiative wireless energy transfer operating at 6.78 MHz and 13.56 MHz is presented. By employing multi-coil approach, measured power transfer efficiency for a symmetrical link separated at axial distance of 30 mm are 72.34% and 74.02% at the respective frequency bands. When operating distance is varied between 30 mm to 38 mm, consistency of simulated peak transfer efficiency above 50% is achievable.